Cardiac Doppler Parameters and Progress in Clinical Manifestation of Primary Lower Extremity Varicose Veins: A Prospective Study in China - Zhang, Jia; Wu, Zhoupeng; Feng, Qingbo; Huang, He; Ma, Yukui (Frontiers in Surgery, 2022)
Objective To investigate the features of cardiac Doppler parameters in patients with primary lower extremity varicose veins in China. Materials and methods We performed prospective statistical analysis of cardiac Doppler parameters between 129 Chinese varicose vein patients and normal controls. Furthermore, we evaluated the relationship between cardiac Doppler and the progress or severity of lower extremity varicose veins. Results Compared with normal controls, patients with primary varicose veins had significantly lower early mitral and tricuspid diastolic inflow and annular velocities (E- and e′-waves), significantly higher late mitral and tricuspid diastolic inflow and annular velocities (A- and a′-waves), significantly higher mitral systolic annular velocities (s′-wave) and significantly lower mitral and tricuspid E/A ratio. There was no significant association between deep venous reflux (DVR) of the lower extremities and cardiac Doppler parameters. The relationship between Clinical Etiological Anatomical Pathophysiological (CEAP) clinical class and cardiac Doppler parameters showed on: In comparison with normal control, all cardiac Doppler parameters of C2 clinical class patients were basically unchanged, but the cardiac Doppler parameters of the C3 or higher CEAP class patients changed. So we found potential CEAP grade cut-off value (C3) linked to statistical changes in cardiac Doppler parameters. Conclusion Cardiac Doppler parameters in primary varicose vein patients could be indeed different from those of normal people, especially for C3 class or higher CEAP clinical class patients. Therefore, for those patients, preoperative echocardiography can be used to evaluate cardiac hemodynamic changes, but large-scale clinical promotion requires further large sample studies.